Research Review: Engaging men: a multi‐level model to support father engagement. Issue 1 (30th July 2015) - Pfitzner, Naomi; Humphreys, Cathy; Hegarty, Kelsey
Abstract: While there is a growing body of work on using fatherhood as an opportunity to engage men in strategies to prevent child maltreatment and further acts of domestic violence, there is limited research on engaging fathers in strategies to prevent domestic violence from occurring. To fill this gap in the literature, this paper explores existing father engagement frameworks used in child and family services and supports a multi‐level model of father engagement for domestic violence primary prevention. Drawing together evidence about father engagement from a range of studies, including the more general parenting literature, we describe factors that influence father engagement based on an analysis of the literature. These factors include accessibility, staff attitudes and behaviours, programme marketing and the format of service provision.